2013
DOI: 10.4097/kjae.2013.65.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative risk factors for prolonged mechanical ventilation after liver transplantation due to acute liver failure

Abstract: BackgroundAcute liver failure (ALF) is a rapidly progressing and fatal disease for which liver transplantation (LT) is the only treatment. Posttransplant mechanical ventilation tends to be more prolonged in patients with ALF than in other LT patients. The present study examined the clinical effects of prolonged posttransplant mechanical ventilation (PMV), and identified risk factors for PMV following LT for ALF.MethodsWe reviewed data of patients undergoing LT for ALF between January 2005 and June 2011. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
5
2
Order By: Relevance
“…In a recent study by Prasad et al (14) the volume of blood products used in patients undergoing orthotopic liver transplantation was found to be a significant predictor of postoperative poor outcome. In our study, although the amount of transfusion of erythrocyte suspension and FFP was very low compared with the other studies (15,16), it was found to be higher in the prolonged mechanical ventilation group than the other group without reaching statistical significance. On the other hand, the use of cryopresipitat was found to be statistically significantly higher in the prolonged mechanical ventilation group.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In a recent study by Prasad et al (14) the volume of blood products used in patients undergoing orthotopic liver transplantation was found to be a significant predictor of postoperative poor outcome. In our study, although the amount of transfusion of erythrocyte suspension and FFP was very low compared with the other studies (15,16), it was found to be higher in the prolonged mechanical ventilation group than the other group without reaching statistical significance. On the other hand, the use of cryopresipitat was found to be statistically significantly higher in the prolonged mechanical ventilation group.…”
Section: Discussioncontrasting
confidence: 83%
“…Another risk factor for prolonged mechanical ventilation is preoperative poor condition. There are many studies in the literature that show that high ASA and MELD scores are associated with poor outcomes (14,15,23). In our study, ASA and MELD scores were significantly higher in the prolonged mechanical ventilation group, but the effect of age, gender and comorbid disease on mechanical ventilation duration was not shown.…”
Section: Discussioncontrasting
confidence: 65%
“…Many current studies have found that a high MELD score is a risk factor for PMV after liver transplantation [14,26,29]. The MELD score is a commonly used score to evaluate the severity of endstage liver disease and has a valuable correlation with the prognosis of patients after liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged mechanical ventilation after LT is associated with worse outcomes [ 29 , 30 , 31 ]. The first study describing the early benefits of extubation after LT in combination with restrictive fluid management was published in 1990 by Rossaint et al [ 32 ].…”
Section: Mechanical Ventilation After Transplantationmentioning
confidence: 99%